2010
DOI: 10.1007/s12031-010-9369-2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7 Nicotinic Acetylcholine Receptor Expression and Activity During Neuronal Differentiation of PC12 Pheochromocytoma Cells

Abstract: Nicotinic acetylcholine receptors (nAChR) exert pivotal roles in synaptic transmission, neuroprotection and differentiation. Particularly, homomeric alpha7 receptors participate in neurite outgrowth, presynaptic control of neurotransmitter release and Ca2+ influx. However, the study of recombinant alpha7 nAChRs in transfected cell lines is difficult due to low expression of functional receptor channels. We show that PC12 pheochromocytoma cells induced to differentiation into neurons are an adequate model for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
(59 reference statements)
2
19
0
1
Order By: Relevance
“…29,30 It was also shown that the differentiation of PC12 cells with the nerve growth factor increases the expression of various receptors implicated in A β 42 endocytosis to the levels observed in central nervous system derived neuronal cell lines. 31,32 Our studies have clearly demonstrated that A β 40 uptake mechanisms observed in PC12 cells are verifiable in primary rat embryonic cortical neurons. 9 …”
Section: Discussionmentioning
confidence: 53%
“…29,30 It was also shown that the differentiation of PC12 cells with the nerve growth factor increases the expression of various receptors implicated in A β 42 endocytosis to the levels observed in central nervous system derived neuronal cell lines. 31,32 Our studies have clearly demonstrated that A β 40 uptake mechanisms observed in PC12 cells are verifiable in primary rat embryonic cortical neurons. 9 …”
Section: Discussionmentioning
confidence: 53%
“…S4). In these experiments, we used neuronally differentiated PC12 cells that predominantly express a3b4 nAChR subtype (Avila et al, 2003;Henderson et al, 1994) and gave larger and more reproducible amperometric responses to ACh as found by us and other investigators (Nery et al, 2010) compared with un-differentiated PC12 cells.…”
Section: Effect Of Human Cst Variants On Blockade Of Acetylcholine-evmentioning
confidence: 95%
“…RT-PCR analysis revealed that such cells express α3, α5, α7, β2 and β4 nAChR subunits, and measurements in the presence of methyllycaconitine (MLA) indicated that, on day 2 following induction to neuronal differentiation, α7 receptors contributed about 50% of cholinergic receptor-mediated whole cell currents [36].…”
Section: Resultsmentioning
confidence: 99%
“…PC12 cells (ATCC, catalogue # CRL-1721) were cultured and induced to neuronal differentiation as described [24], [36]. Briefly, PC12 cells were cultured in DMEM (Invitrogen, Life Technologies, Carlsbad, CA, USA) in the presence of 10% FBS (Cultilab, Campinas, São Paulo, Brazil), 5% horse serum (Invitrogen, Life Technologies, Carlsbad, CA, USA), streptomycin (100 µg/ml), penicillin (100 U/ml – Sigma-Aldrich, St. Louis, MO, USA) and 1 mM sodium pyruvate (Invitrogen, Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation